Konsep Pengembangan Ruang Terbuka Hijau (RTH) Pada Permukiman Kepadatan Tinggi - Susilowati, Indah; Nurini, Nurini (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2013)
Surakarta has a concept of â€œEco Cultural Cityâ€ which has been realized by performing efforts to increase the quality and quantity of green open space, especially in high density residential. Development of a green open space in high-density residentials are an interesting phenomenon to study with raised a research questions: how does the development concept of green open space in high density residential? Purpose of this study is to develop the development concept of green open space in high density settlements. The objects of this research are assessing the characteristics in high density residential, examines the characteristics ofÂ  green open space inÂ  high- density residential, analyze green open space typology in high density residential, and analyzes development concept of green open space in high density residential through the â€œhuman settlementâ€ concept. This research was conducted using a quantitative approach. The development concept of green open space, in the concept of â€œhuman settlementâ€, geared towards the function development of green open space in achieving â€œnatureâ€ and â€œsocietyâ€ elements on each green open space typology formed. One form of the development concept of green space is done by optimizing land through planting medium pots of plants.